An Oxalyl-CoA Synthetase Is Involved in Oxalate Degradation and Aluminum Tolerance . Issue 3 (20th September 2016) - Lou, He Qiang; Fan, Wei; Xu, Jia Meng; Gong, Yu Long; Jin, Jian Feng; Chen, Wei Wei; Liu, Ling Yu; Hai, Mei Rong; Yang, Jian Li; Zheng, Shao Jian
Abstract : A Vigna umbellata oxalyl-CoA synthetase, VuAAE3, confers tolerance to Al stress by regulating cytosolic oxalate metabolism. Abstract: Acyl Activating Enzyme3 (AAE3) was identified to be involved in the catabolism of oxalate, which is critical for seed development and defense against fungal pathogens. However, the role of AAE3 protein in abiotic stress responses is unknown. Here, we investigated the role of rice bean ( Vigna umbellata ) VuAAE3 in Al tolerance. Recombinant VuAAE3 protein has specific activity against oxalate, with K m = 121 ± 8.2 µm and V max of 7.7 ± 0.88 µmol min −1 mg −1 protein, indicating it functions as an oxalyl-CoA synthetase. VuAAE3-GFP localization suggested that this enzyme is a soluble protein with no specific subcellular localization. Quantitative reverse transcription-PCR and VuAAE3 promoter-GUS reporter analysis showed that the expression induction of VuAAE3 is mainly confined to rice bean root tips. Accumulation of oxalate was induced rapidly by Al stress in rice bean root tips, and exogenous application of oxalate resulted in the inhibition of root elongation and VuAAE3 expression induction, suggesting that oxalate accumulation is involved in Al-induced root growth inhibition. Furthermore, overexpression of VuAAE3 in tobacco ( Nicotiana tabacum ) resulted in the increase of Al tolerance, which was associated with the decrease of oxalate accumulation. In addition, NtMATE and NtALS3 expression showed no difference between transgenic lines and wild-type plants. Taken together, our results suggest that VuAAE3-dependent turnover of oxalate plays a critical role in Al tolerance mechanisms.